1996
DOI: 10.1002/j.1556-6676.1996.tb01872.x
|View full text |Cite
|
Sign up to set email alerts
|

The Structured Peer Consultation Model for School Counselors

Abstract: School counselors typically receive little or no supervision of their counseling. Results of an evaluation of the Structured Peer Consultation Model for School Counselors indicate that the model may help meet the needs of school counselors for ongoing feedback on their counseling with student-clients.Electronic Journal: To print this article select pages 90-94. TOC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 11 publications
0
52
0
1
Order By: Relevance
“…Although three models are listed, all are based in the Remley, Benshoff, and Mowbray (1987) format. This is a true consultation model, with peers taking turns being supervisor and supervisee without any oversight by others, although an orientation and training session was provided to participants in one study (Benshoff & Paisley, 1996).…”
Section: Dyadic Peer Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although three models are listed, all are based in the Remley, Benshoff, and Mowbray (1987) format. This is a true consultation model, with peers taking turns being supervisor and supervisee without any oversight by others, although an orientation and training session was provided to participants in one study (Benshoff & Paisley, 1996).…”
Section: Dyadic Peer Modelsmentioning
confidence: 99%
“…Benshoff found no significant differences between the two groups' post‐test self‐ratings of counselling effectiveness. Benshoff and Paisley (1996) employed the model with school counsellors ( n = 20) who, in a pilot study, completed 16 evaluation items. Participants gave very positive ratings of their experience overall and reported that the model had helped them develop their counselling and consulting skills.…”
Section: Dyadic Peer Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies focusing on post-degree supervision of professional school counselors have documented the underutilized practice of school counselor supervision in schools and included recommendations for the practice and delivery of supervision for school counseling professionals who have completed their formal educational training. Samples of these recommendations include peer supervision (Agnew, Vaught, Getz, & Fortune, 2000;Borders, 1991;Crutchfield & Borders, 1997), peer consultation (Benshoff & Paisley, 1996), group supervision Gainor & Constantine, 2002), and clinical supervision (Henderson & Lampe, 1992;Sutton & Page, 1994). Several authors have focused their work specifically on theories, models, and modalities of supervision that attempt to address the practice of supervision for professional school counselors (Borders, 1989;Getz 1999;Nelson & Johnson, 1999;Page, Pietrzak, & Sutton, 2001;Peace, 1995;Protivnak, 2003).…”
mentioning
confidence: 99%
“…3. Utilize supervision models that foster interdependence among counselor trainees such as the Structured Peer Consultation Model for School Counselors (SPCM-SC, Benshoff & Paisley, 1996). 4.…”
Section: Implications For Supervision Practicementioning
confidence: 99%